Configuration tool for generating multi-type and multi-robot work cell layout - Rahman, Muhamad Arfauz A; Shikder, Kaafi N.; Maropoulos, Paul G.; Mohamad, Effendi; Rahman, Azrul Azwan Abdul; Salleh, Mohd Rizal (2023)
With the continuous increment in the installation and industrial robots in manufacturing industries, it is getting increasingly complicated for engineers to design efficient layouts for these robot work cells. This study has attempted to solve this problem by developing a configuration tool that would automatically propose and simulate a robot work cell layout upon receiving input data from the user with the help of a Graphical User Interface (GUI). This GUI and the underlying solution algorithms embedded in the configuration tool have been developed employing Microsoft Visual Basic, which is integrated with SOLIDWORKS API to demonstrate the layout design solutions in SOLIDWORKS directly. Five types of robot models have been considered in this study: with each of these robots being 6-DOF and primarily used for welding tasks. The developed configuration tool can produce design solutions for three types of layout shapes: Linear Horizontal/Vertical, Linear Parallel and L-Shaped, for a maximum of ten robots per layout. Specifically, this tool can generate layout design solutions for approximately 12 million combinations of these five types of robots per layout or about 36 million types of solutions. This configuration tool can potentially assist the design engineers in simplifying this complicated robot work cell layout and, therefore, can act as a guiding tool for effective cell layout designs. At this stage, the developed tool is preliminary work involving only simulation works.